Pre-infestation of Tomato Plants by Aphids Modulates Transmission-Acquisition Relationship among Whiteflies, Tomato Yellow Leaf Curl Virus (TYLCV) and Plants - Tan, Xiao L.; Chen, Ju L.; Benelli, Giovanni; Desneux, Nicolas; Yang, Xue Q.; Liu, Tong X.; Ge, Feng (Frontiers in Plant Science, 2017)
Herbivory defense systems in plants are largely regulated by jasmonate-(JA) and salicylate-(SA) signaling pathways. Such defense mechanisms may impact insect feeding dynamic, may also affect the transmission-acquisition relationship among virus, plants and vectoring insects. In the context of the tomato – whitefly – Tomato Yellow Leaf Curl Virus (TYLCV) biological model, we tested the impact of pre-infesting plants with a non-vector insect (aphid Myzus persicae) on feeding dynamics of a vector insect (whitefly Bemisia tabaci) as well as virus transmission-acquisition. We showed that an aphid herbivory period of 0–48 h led to a transient systemic increase of virus concentration in the host plant (root, stem, and leaf), with the same pattern observed in whiteflies feeding on aphid-infested plants. We used real-time quantitative PCR to study the expression of key genes of the SA- and JA-signaling pathways, as well as electrical penetration graph (EPG) to characterize the impact of aphid pre-infestation on whitefly feeding during TYLCV transmission (whitefly to tomato) and acquisition (tomato to whitefly). The impact of the duration of aphid pre-infestation (0, 24, or 48 h) on phloem feeding by whitefly (E2) during the transmission phase was similar to that of global whitefly feeding behavior (E1, E2 and probing duration) during the acquisition phase. In addition, we observed that a longer phase of aphid pre-infestation prior to virus transmission by whitefly led to the up-regulation and down-regulation of SA- and JA-signaling pathway genes, respectively. These results demonstrated a significant impact of aphid pre-infestation on the tomato – whitefly – TYLCV system. Transmission and acquisition of TYLCV was positively correlated with feeding activity of B. tabaci, and both were mediated by the SA- and JA-pathways. TYLCV concentration during the transmission phases was modulated by up- and down-regulation of SA- and JA-pathways, respectively. The two pathways were inconsistent during the acquisition phase; SA- related genes were up-regulated, whereas those up- and down-stream of the JA pathway showed a more complex relationship. These findings enhance our understanding of plant – herbivore – virus interactions, which are potentially important for development of ecologically sound pest and pathogen management programs.